Explaining unobserved heterogeneity of food safety behavioral intention: a sequential mixed method approach - Lin, Naiqing (Kansas State University, 2018)
In 2015, 902 foodborne illness outbreaks were reported to the Centers for Disease Control and Prevention, resulting in 15,202 illnesses, 950 hospitalizations, and 15 deaths. Previous literature from both survey and observational studies have reported low conformity with the U.S. Food and Drug Administration (FDA) Food Code guidelines. To effectively reduce foodborne illnesses, foodservice managers and food handlers must perform proper food safety behaviors. Therefore, the purpose of this project is to identify and explain the unobserved cognitive processes within food safety behavioral intention. An explanatory sequential mixed methods design was utilized. First, a systematic review and meta-analyses of the existing literature were conducted to quantify statistical power better and summarize the effect sizes with conflicting studies. Then, an in-depth qualitative study was conducted to help explain the statistical results. Using existing observed cognitive variables grounded by the Theory of Planned Behavior, the key idea is that the qualitative inquiry was built on the quantitative results. Thus, the syntheses of both studies help explained the unobserved heterogeneity information. Study 1 included a total of 1,550 studies for screening with 46 records meeting the inclusion criteria for analyses. The overall random effect size (r) was 0.282 (p < 0.001) providing collective evidence that the TPB constructs predict food safety behavioral intention. Subjective norms were noted as the most influencial variable to food safety behavioral intention. Studies with employee motivational constructs tend to show the most positive effect on food safety intention relationships. However, the Theory of Planned Behavior model only explained a combined 22% of total true effect variance. Thus, a considerable amount of the variance (78%) within food safety behavioral intention is still unexplained. Study 2 used an online questionnaire to measure individual-level norms. Open-ended questions (14) helped create qualitative narrative texts for analyses and establishing a demographic profile of the participants. A total of 104 responses from foodservice and restaurant employees were documented for coding. Most participants were female, with a mean age of 36 with an average of about 11 years of foodservice industry experiences. The results indicated that employees are usually not influenced of other managers or coworker’s approval or disapproval of their behavior. Rather, their behavior is guided by an innate motivation for moral consideration and ethical reasoning. The data further indicated that participants experience injunctive (subjective) norms, but more from a retrospective formation, rather than a forward-looking expectance regarding food safety practices. Intrinsic motivation should be an important antecedent to form normative beliefs of food safety-related behaviors. The findings of the study results challenge the previous understanding of path directions regarding normative pressure. Limitations and future studies related to maximize food safety behavioral intentions were discussed.
Keywords: Heterogeneity Ratio; Descriptive Norms; Theory of Planned Behavior; Meta-Analyses; Explanatory Design